The social media response to the rollout of legalized cannabis retail in Ontario, Canada. (July 2021) - Aversa, Joseph; Jacobson, Jenna; Hernandez, Tony; Cleave, Evan; Macdonald, Michael; Dizonno, Stephanie
Abstract: With Canada becoming the first G20 country to legalize the recreational use of cannabis, there has been increasing interest in the emergence of this new retail market. The research utilizes social media analytics to analyze the public's response to the rollout of the government-controlled cannabis retail stores: Ontario Cannabis Store (OCS). The research analyzes 17, 162 tweets mentioning the OCS (@ONCannabisStore) on Twitter in the one-year period following the legalization of recreational cannabis. Using thematic analysis, 19 codes are identified and further categorized under six themes—i.e., consignment, product, retail model, policy, producers, and consumers. The research provides valuable insight into the public's perceptions of the newly legalized cannabis retail market on social media. As a practical implication of the research, key concerns and issues with the initial retail rollout are identified, which provides insight into the evolution of an illegal to legal retail market. The methods can be used by future researchers, policy makers, and emerging cannabis retailers to gather and understand cannabis consumers' opinions on social media. Furthermore, the findings can be leveraged to inform future government policies and decisions around the emergence of this new retail sector.